Art practice as research: Inquiry in the visual arts - Sullivan, Graeme (London Sage Publications, 2005)
F. Scott Fitzgerald famously said that the test of a 'first rate intelligence' is 'the ability to hold two opposed ideas in the mind and still retain the ability to function.'In this book, his magnum opus, artist and scholar Graeme Sullivan shows us a first rate mind at work. He convincingly straddles the often wide gaps between art and science, mind and body, research and practice, teaching and doing, traditional and postmodern views of education and of art, creative and critical thinking. Indeed, as his enigmatic title indicates, he is actually able to keep three usually disparate concepts-art, research, and practice-in mind at the same time. Through his skilled use of compelling sidebars and apt illustrations, Sullivan shows that he can practice what he preaches. I have been arguing with and learning from Graeme for thirty years and am grateful that he has the opportunity to share his provocative ideas and insights with a wider readership. Indeed, whether or not we agree with every contention, he heightens our own intelligences. -Howard Gardner, Harvard Graduate School of Education, Author of Five Minds for the Future Substantially updated and revised, Art Practice as Research, Second Edition presents a compelling theory that the creative and cultural inquiry undertaken by artists is a form of research. Sullivan argues that legitimate research goals can be achieved by choosing different methods than those offered by the social sciences.. Artists emphasize the role of the imaginative intellect in creating, criticizing, and constructing knowledge that is not only new but also has the capacity to transform human understanding. student of art and art education in art schools and schools of education." (Susan Paterson )